Environmental impact and recovery of the Bohai Sea following the 2011 oil spill. (August 2020) - Wang, Yujue; Lee, Kenneth; Liu, Dongyan; Guo, Jie; Han, Qiuying; Liu, Xihan; Zhang, Jingjing
Abstract: The 2011 spill at platforms B and C of the Penglai 19-3 oil field in the Bohai Sea has been the worst oil spill accident in China. To assess long-term effects, a comprehensive monitoring program of chemical and biological variables (within a 2.2 km radius of the spill site) was conducted five years after the spill. Comparison of nutrient, Chl- a and oil concentrations in seawater, TOC, PAHs, heavy metals concentrations within the sediments, and the abundance and biomass of macrobenthic organisms to values obtained before and after the oil spill in previous studies indicate habitat recovery has occurred within the Bohai Sea following the episodic oil release. Observed elevated oil concentration in the water column and higher concentrations of two heavy metals, five PAHs, TOC, TOC/TN and lower values of δ 13 C, together with a reduction in macrobenthic biomass in near-field samples, suggest the influence of contaminants from chronic releases of oil and operational waste discharges within the vicinity of the oil platforms. Graphical abstract: Image 1 Highlights: Ecological impacts of an oil spill in the Bohai Sea were studied. Significant levels of habitat recovery occurred within 5 years. Environment near the platform remain a concern as a result of chronic inputs. Abstract : Significant levels of habitat recovery occurred in the Bohai Sea five years after the oil spill, however, the environment near the platform remains a concern as a result of chronic inputs.